Makna Doa Menurut Perspektif Paulus Dalam Surat-Suratnya Dan Implementasinya Terhadap Kehidupan Orang Percaya - Alferdi Alferdi; Eirene Imiawati Rindi (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2022)
The purpose of writing this article is to analyze Paul's understanding of prayer, so that prayer is well understood by believers, and not just a formality. Being a believer is certainly not enough just to believe. In living this belief, a person should have a good relationship between himself and the Creator. In Christianity, prayer is a link between people and God. However, some people sometimes misunderstand the meaning of prayer in their lives. Some people think that prayer has the purpose of being able to talk to God only when asking God, or only when in a struggle to come to God. When these things are kept by believers, it can be concluded that their understanding of prayer is still shallow. The writing of this article uses a descriptive qualitative method with a literature study approach. The author will explore information about Paul's understanding of prayer, by utilizing related journals and books. This research shows that Paul understands prayer as a suggestion to build a more intimate relationship with God. Besides that, prayer is also a suggestion to gain God's power and love. That is what believers must understand, so that in offering every prayer to God it is truly based on humility and sincerity.